KOMPETENSI GURU MI DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN DIGITAL BERBASIS GEDSI - Andrian Gandi Wijanarko; Joni; Moh Syafi; Rifqil Muslim; Ahmad Rizky Latyf (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
This research aims to strengthen teachers' competence in creating GEDSI-based digital learning media.. This article uses the PAR method with the subject of a class V MI teacher in Tegalrejo, Magelang. The instrument used is in the form of teacher competency understanding sheets in compiling GEDSI-based digital learning media. The results of this service are 85% in the very good category and 15% in the good category. In addition, have awareness related to media development. Innovate in integrating natural science material with digital technology and mainstream GEDSI. Third, Include payloads/characters based on GEDSI. Develop evaluation tools and implement their work in their respective institutions.required for computerization. Development of digital learning media adapted to GEDSI as the foundation of inclusive education in order to develop abilities, shape character, and national civilization.